Percepção ambiental no manejo do resíduo domiciliar em residências na área urbana do município de Frederico Westphalen - RS - Silva, Rodrigo Coutinho da (2014)
One of the problems that affect the population´s quality life is the management of solid residues, among them, the domestic garbage. The current work shows information on the packaging of the domestic garbage in residences of Frederico Westphalen urban area and also, the population knowledge on the correct way of separation of garbage, the adequate local for it collect, the soil impacts caused by the garbage on the ground, the relationship between waste and the public health, the waste composting and vegetable garden, and the pets that feed of the domestic residues. The orientation on the best way of managing the solid residues in the visited residences was accomplished standing out the correct separation and packaging of waste. The research reached all neighborhoods of the city, what showed a great social difference among the visited places. The visited residences, where a questionnaire containing fourteen questions related to this work subject was applied. This way, different situations inserted in the urban perimeter of the city were analyzed. The results analysis revealed the population is aware the need of the environment preservation, to assure better life and health conditions. However, the environmental education guiding the population on the correct waste management in their residences is indispensable, because several significant cases of disorder in the domestic garbage packaging were diagnosed.